Teachers’ Dispositions Toward Mindfulness in EFL/ESL Classrooms in Teacher-Student Interpersonal Relationships - Song, Xiaochuan; He, Xuan (Frontiers in Psychology, 2021)
The psychological factors of English as a foreign language (EFL) and English as a second language (ESL) teachers have significant roles in any language learning context. Previous studies in the related literature have shown that L2 learners’ learning, psychological factors, and emotional factors are closely related to teachers’ psychological factors. Mindfulness as one of the psychological attributes of L2 teachers and as a complex and multi-faceted construct influence l2 teachers’ professional development. Hence, this study aims to review the notion of mindfulness and its role in L2 teaching as a profession and pave a way for further research, highlighting its indispensable role in teacher-student relationships. To achieve this goal, this study has reviewed the theoretical perspectives of mindfulness, the construct of mindful L2 teaching education, and mindfulness as a closely related concept to teacher well-being. Based on the findings, some pedagogical implications for the policymakers, teacher-trainers, materials developers, L2 teachers, and learners are provided. Finally, directions for future research are suggested to the interested L2 researchers.